If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(9 + -1x) = 0 (9 * 10 + -1x * 10) = 0 (90 + -10x) = 0 Solving 90 + -10x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-90' to each side of the equation. 90 + -90 + -10x = 0 + -90 Combine like terms: 90 + -90 = 0 0 + -10x = 0 + -90 -10x = 0 + -90 Combine like terms: 0 + -90 = -90 -10x = -90 Divide each side by '-10'. x = 9 Simplifying x = 9
| 35-(2c+3)=2(c-6)+c | | -7p-39=5(-5p+30) | | 3y+6x=360 | | 10x^2-17x+34=7x^2-26x+28 | | -15+-14e=-33 | | -13-8j=-5 | | 9m+6=96# | | 4b+6=-22 | | 4(p+5)=2 | | -43=13p-65 | | 0=x^4+4x^2-32 | | y=(-8)(1) | | (X+10)(x)=144 | | 21-4j=13 | | 11-3*3-1= | | -2(x+y)+9=1 | | -7=6m-7m | | 6(X-1)=2x+6 | | (x-2)*(x+3)=x*x-8 | | 17d-5=3d | | y=-16t^2+468 | | 2x-13-6x+3=28-4-2-3x | | 20+1x=25+.75x | | 7+v(1)=6+v | | 9-5m+2=7+2m | | 9n-9=-126 | | 45=3 | | 16c+8=3c | | -9-6g=-33 | | Sen(4x)-cos(4x)-1=0 | | -6+p=14 | | 9*243= |